Large Gastrointestinal Stromal Tumor Mimicking A Gynecologic Tumor - Sew-Khee Yeat; Heng-Ju Chen; Hun-Shan Pan; Yu-Hung Lin; Jiann-Loung Hwang; Lee-Wen Huang (Elsevier, 2005)
Objective: Gastrointestinal stromal tumors (GISTs) are a group of uncommon bowel tumors. We report two cases of GISTs arising from the ileum and jejunum, both of which appeared to mimic a gynecologic tumor. Case Report: In the first case, an 83-year-old, postmenopausal, woman presented with poor appetite, abdominal fullness and constipation for the preceding 3-4 days. Physical examination and imaging studies revealed a huge pelvic mass, suggestive of a huge cystic degenerated myoma. An exploratory laparotomy revealed a large tumor originating from the ileum, and immunohistochemical stains confirmed the presence of CD-117. In the second case, a 48-year-old woman presented with intermittent right lower abdominal pain and urinary frequency over the preceding 4 months. Physical examination and imaging studies revealed a pelvic mass of 21-week-gestational size. An exploratory laparotomy showed a huge fragile pelvic tumor, measuring 20 × 20 cm, arising from the jejunum. Immunohistochemical staining confirmed the presence of CD-117. Conclusion: GISTs express c-kit proteins (CD-117) on immunohistochemistry. They may mimic gynecologic tumors since they share the same pelvic cavity. One should always consider GISTs as part of the differential diagnosis in pelvic tumors.